2018
DOI: 10.20944/preprints201809.0273.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Low-Level Laser Therapy with Diode Laser for the Enhancement of the Orthodontic Tooth Movement: a Split-Mouth Study

Abstract: This study evaluated the effect of low-level laser irradiation induces by diode laser on the speed of orthodontic tooth movement of canines submitted to initial retraction. Twenty-four mandibular canines were retracted by using NiTi spring (force of 150 g/side). Thirteen of those were irradiated with a diode laser 980-nm diode laser (Wiser Laser Doctor Smile, Lambda) operating at an 810-nm wavelength (1 W of output power, continuous wave of 66.7 J/cm2) that was equipped with a 0.6-mm optical fiber in continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…According to a systematic review, LLLT significantly increased osteoclastic but not osteoblastic activity during the initial phases of tooth movement, and that the osteoclastic activity was dose-dependent. 33 Cruz et al, 20 Youssef et al, 22 and da Silva Sousa et al 23 found the significantly greater velocity of tooth movement with LLLT. Limpanichkul et al 21 did not find an increase in tooth velocity.…”
Section: R Eview R Esultsmentioning
confidence: 96%
See 1 more Smart Citation
“…According to a systematic review, LLLT significantly increased osteoclastic but not osteoblastic activity during the initial phases of tooth movement, and that the osteoclastic activity was dose-dependent. 33 Cruz et al, 20 Youssef et al, 22 and da Silva Sousa et al 23 found the significantly greater velocity of tooth movement with LLLT. Limpanichkul et al 21 did not find an increase in tooth velocity.…”
Section: R Eview R Esultsmentioning
confidence: 96%
“…Eleven articles remaining were retrieved and their references cross-checked. This yielded an additional 3 articles making a total of 14 articles that were systematically reviewed 12 , 20 33 ( Tables 2 and 3 ). Further nine studies were considered for meta-analysis with similar outcomes ( Fig.…”
Section: R Eview R Esultsmentioning
confidence: 99%